Religiosity, stress, and depressive symptoms among nursing and medical students during the middle stage of the COVID-19 pandemic: A cross-sectional study in Morocco - Rammouz, Ismail; Lahlou, Laila; Salehddine, Zineb; Eloumary, Omar; Laaraj, Hicham; Ouhamou, Mina; Mouhadi, Khalid; Doufik, Jalal; Aalouane, Rachid; Boujraf, Said (Frontiers in Psychiatry, 2023)
Among nurses and medical students, many studies showed higher prevalence of depression and stress than general population. Religiosity and spirituality are common in Muslim countries, and they usually are used as a mean strategy coping. Our objective was to evaluate the association between religious actions, depressive symptoms and stress among nursing and medical students from all three first years in Agadir University (Morocco) A sample of different stages of nursing and medical students was recruited. The religiosity was assessed by Muslim Belief Into Action. The depressive symptoms and stress were respectively assessed by Beck Depression Inventory (BDI II) and Perceived Stress Scale (PSS) Four hundred and thirteen students participated in this study. Our results showed high prevalence of depressive symptoms (62,2 %) and stress. (66,8 %). The depression scores were higher in the two first years, among female medical students, and nursing students with significant differences. The religiosity was greater among students without depression than among students with depression (p<0.001). In the multivariate regression the BIAC score of religiosity was not risk factor neither protective factor of depression Prospective studies are needed to further investigate this association and how religiosity improves the mental health. Which would contribute to improve academic performances and wellbeing among medical and nursing students.